2023
DOI: 10.1037/mac0000074
|View full text |Cite
|
Sign up to set email alerts
|

How susceptible are you? Using feedback and monitoring to reduce the influence of false information.

Abstract: Exposures to false ideas can result in that information being remembered later, inappropriately identified as valid, and reproduced on subsequent tasks. Previous work has shown that evaluative tasks beneficially increase people's use of correct prior knowledge over presented inaccuracies but often rely on explicit instructions to instantiate an evaluative mindset. We examined whether and how confronting people about their potential susceptibility to the influence of false information might motivate evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Determining best practices for encouraging evaluation in ways that are not seen as manipulative, and that offer access to useful epistemic resources, are critical in the design of social media experiences. Recent work indicates behavioral nudges that encourage evaluative mindsets might be applied before or during social media interactions to exert downstream benefits (Pennycook et al, 2020, 2021; Salovich & Rapp, 2023). Perhaps behavioral nudges would be particularly powerful if seen by people as connecting to and supporting their accuracy values without undermining their information-seeking goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining best practices for encouraging evaluation in ways that are not seen as manipulative, and that offer access to useful epistemic resources, are critical in the design of social media experiences. Recent work indicates behavioral nudges that encourage evaluative mindsets might be applied before or during social media interactions to exert downstream benefits (Pennycook et al, 2020, 2021; Salovich & Rapp, 2023). Perhaps behavioral nudges would be particularly powerful if seen by people as connecting to and supporting their accuracy values without undermining their information-seeking goals.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previously published general knowledge norms (Tauber et al, 2013) and subsequent verification (Salovich et al, 2022), half ( n = 36) of the Tweets referenced information likely known to participants and designated as easy items, and the other half of the Tweets referenced information less likely to be known to participants and designated as hard items 1 . We included easy and hard items in line with the previous work, which has demonstrated that relevant prior knowledge is an important influence on people’s evaluations (e.g., it is easier to reject inaccurate information if people already possess accurate understandings; Kendeou & O’Brien, 2014; Richter et al, 2009; Salovich & Rapp, 2023). At test, all participants responded to open-ended questions related to the 72 Tweets (e.g., “What is the capital of France?”).…”
Section: Methodsmentioning
confidence: 99%
“…The broader feedback and performance literature outlined above (e.g., Butler et al, 2007;Smith & Kimball, 2010;Rowland, 2014) suggests this is likely. Further, recent work (Salovich & Rapp, 2023) addressing the influence of false information, in particular, found that receiving either positive or negative performance feedback about susceptibility to inaccurate information led to the reproduction of fewer false claims and more correct ones. This finding undergirds our approach.…”
Section: Feedback Effects On (Over)confidence and News Discernmentmentioning
confidence: 99%
“…In this study, we examine whether providing feedback about relative performance on a news veracity discernment task -above or below average -can help news consumers better calibrate their perceived ability (Salovich & Rapp, 2023). More importantly, though, we also test whether this results in a concurrent improvement in discernment itself, as respondents may reconsider their strategies and heuristics for judging news veracity in light of feedback (Brown et al, 2019).…”
mentioning
confidence: 99%
“…Thus, it was exciting to see two new articles in this section that demonstrate novel ways to induce an evaluative mindset. In the first, Salovich and Rapp (2023) found that people are less susceptible to misinformation when they know that their performance is being monitored (either because they received feedback or were simply told that their susceptibility to misinformation was being monitored). People are often unmotivated to do the deep thinking required by an evaluative mindset; however, the social pressure of being evaluated may be a useful motivational push.…”
Section: Simple Ways To Encourage Evaluative Mindsetsmentioning
confidence: 99%